PENGARUH CURRENT RATIO DAN DEBT TO ASSET RATIO TERHADAP RETURN ON ASSET PADA PT PETROSEA TBK PERIODE 2011-2022 - Dwi Maharani, Ananda; Intan Sari, Widya (Journal of Research and Publication Innovation, 2024)
The purpose of this study was determine the influence of Current Ratio and Debt to Asset Ratio both partially and simultaneously on the Return  On Asset of PT Petrosea Tbk in 2011-2022. This type of research is associative with quantitative methods using the SPSS version 27 application. Based on the test results, it was found that partially the Current Ratio (CR) variable with a t value of -4,156 > t table 2,262 and significant value 0,002 < 0,05 shows that CR has an effect on ROA. While the Debt to Asset Ratio (DAR) partially shows a t value of 0,485 < t table 2,262 and the significant value of DAR is 0,639 > 0,05, showing the results that DAR has no effect on ROA. Simultaneously shows f value 8,704 > F table 4,26 and a significant value of 0,008 < 0,05 that CR and DAR together have an influence on ROA at PT Petrosea Tbk. Based on the R square value of 0,659 or 65,9%. Which means that the variables CR and DAR have an influence contribution of 65,9% on ROA, while the remaining 34,1% is influenced by other variables not examined in this research.